THU0567 Comparative Performance of Fautrel and Yamaguchi Criteria for The Classification of Patients with Adult Onset Still Disease: Preliminary Results. (15th July 2016) - Lebrun, D.; Mestrallet, S.; Dehoux, M.; Golmard, J.-L.; Georgin-Lavialle, S.; Arnaud, L.; Grateau, G.; Pouchot, J.; Fautrel, B.
Abstract : Objectives: To validate Fautrel criteria set for classification of adult onset Still's disease (AOSD), and to establish its discriminative performance to that of the Yamaguchi's set. Methods: We retrospectively reviewed the medical charts of 344 patients who had ferritin and glycosylated ferritin measured at the biochemistry laboratory of Bichat Hospital. Medical informations were extracted via a standardized form. All clinical, biological, imaging features were collected, as well as elements in favor of an alternative diagnosis, specifically symptoms suggestive of other immune-mediated inflammatory diseases (IMID) or active infections. Patients were classified as AOSD or control group, according to a predefined procedure including a review by a group of experts for difficult cases. Algorithms corresponding to Fautrel's and Yamaguchi's classification criteria sets were applied for each patient. Results: 49 AOSD and 229 control patients were included. Fautrel's set displayed a sensitivity of 89.8%, a specificity of 97.8%, and positive and negative predictive values of 89.8% and 97.8% respectively. 5 AOSD diagnoses were missed, and accurately classified as AOSD by standard Yamaguchi's set. The standard Yamaguchi's set – without strict application of exclusion criteria – produced a sensitivity of 95.9%, a specificity of 99.6%, and positive and negative predictive values of 97.9% and 99.1% respectively. 2 AOSD diagnoses were missed and correctly classified with the Fautrel's set. If we applied a stricter definition of exclusion criteria, the sensitivity of Yamaguchi's set decreased to 30.6% (p<0.0001). 34 AOSD diagnoses were also missed. These different sets showed excellent performance, although the differences did not reach statistical significance. Conclusions: Both criteria display high discrimination power in a new cohort of cases and controls. The Fautrel criteria set includes glycosylated ferritin and does not require exclusion criteria. The Yamaguchi criteria set is highly impacted by the way the satisfaction of exclusion criteria were performed. References: Yamaguchi M, Ohta A, Tsunematsu T, Kasukawa R, Mizushima Y, Kashiwagi H, et al. Preliminary criteria for classification of adult Still's disease. The Journal of rheumatology. 1992;19(3):424–30. Fautrel B, Zing E, Golmard JL, Le Moel G, Bissery A, Rioux C, et al. Proposal for a new set of classification criteria for adult-onset still disease. Medicine. 2002;81(3):194–200. Disclosure of Interest: None declared